Antibacterial activity and mechanism of lactobionic acid against Pseudomonas fluorescens and Methicillin-resistant Staphylococcus aureus and its application on whole milk. (February 2020) - Kang, Shimo; Kong, Fanhua; Shi, Xinyang; Han, Hongjiao; Li, Mohan; Guan, Boyuan; Yang, Mei; Cao, Xueyan; Tao, Dongbing; Zheng, Yan; Yue, Xiqing
Abstract: Lactobionic acid (LBA), a polyhydroxy organic acid, is supposed to be a promising candidate for use as multifunctional food additive due to its ability of antibacterial, anti-obesity, etc. The antibacterial activity of LBA has rarely been reported, thus the antibacterial activity and mechanism of LBA against Pseudomonas fluorescens and methicillin-resistant Staphylococcus aureus were investigated. The results of antibacterial activity showed that P. fluorescens was more susceptible to LBA with the lowest minimum inhibitor concentration/minimum bactericidal concentration and that LBA could completely inactivate the selected bacteria. The alkaline phosphatase activity assay, flow cytometry, protein leakage, and sodium dodecyl sulfate polyacrylamide gel electrophoresis demonstrated that LBA could disrupt the integrity of the cell wall and membrane, and the content and activity of bacterial proteins. Scanning electron microscopy and transmission electron microscopy results showed obvious morphological and ultrastructural changes in the bacterial cells, further confirming the cell wall and membrane damages caused by LBA. Moreover, LBA could interact with bacterial DNA via intercalation, to disturb the normal cellular functions. LBA also exhibited antibiofilm formation activity and the ability to inhibit bacterial growth in whole milk. Overall, LBA is expected to be an alternative for novel multifunctional food additive with bacteriostatic action in food industries. Graphical abstract: Image 1 Highlights: Selected bacteria were completely inactivated after lactobionic acid exposure. Lactobionic acid disrupted cell wall and membrane and proteins content and activity. Lactobionic acid bind to genomic DNA and disturb the normal cellular function. Lactobionic acid exhibited antibiofilm formation activity. Lactobionic acid inhibited the growth of selected bacteria in whole milk.